Malaysian healthy diet online survey (MHDOS): study rationale and methodology - Wong, Jyh Eiin; Woon, Fui Chee; Chin, Yit Siew; Teh, Wai Siew; Selamat, Rusidah; Zainuddin, Ahmad Ali; Hendrie, Gilly A; Tee, E. Siong (Nutrition Society of Malaysia, 2022)
Introduction: Access to accurate and timely dietary information is of paramount importance in evaluating and developing well-targeted public health nutrition interventions. However, nationwide nutrition surveys are conducted infrequently because they are very costly to design, conduct and analyse. Dietary assessment tools, which are quick and cost- effective, are needed for population research and regular monitoring of Malaysians’ dietary habits. This paper describes the rationale and methodology of the Malaysian Healthy Diet Online Survey (MHDOS) project, which aims to bridge this knowledge gap on dietary intake of Malaysian adults. The main objective of the two-year project is to develop MHDOS as a valid tool to measure compliance with the Malaysian Dietary Guidelines 2020. Methods: The MHDOS project has three study phases, namely (i) adaptation of an online survey and established diet quality scoring system for Malaysia, (ii) usability, validity and reliability testing of the online survey; and (iii) online survey administration in a nationwide study. The survey will be administered to approximately 10,000 Malaysian adults aged 18-59 years. Discussion: MHDOS consists of 38 questions that measures the quantity, quality and variety of foods consumed. Individuals will receive a diet quality score that reflects their overall compliance with the Malaysian Dietary Guidelines and feedback on how to improve their scores. The findings of the online survey, which serve to complement information between larger surveys, will be useful to measure compliance of Malaysians to national dietary guidelines and inform public health interventions.